ACE2 and ADAM17 Interaction Regulates the Activity of Presympathetic Neurons. Issue 5 (November 2019) - Mukerjee, Snigdha; Gao, Hong; Xu, Jiaxi; Sato, Ryosuke; Zsombok, Andrea; Lazartigues, Eric
Abstract : Brain renin angiotensin system within the paraventricular nucleus plays a critical role in balancing excitatory and inhibitory inputs to modulate sympathetic output and blood pressure regulation. We previously identified ACE2 and ADAM17 as a compensatory enzyme and a sheddase, respectively, involved in brain renin angiotensin system regulation. Here, we investigated the opposing contribution of ACE2 and ADAM17 to hypothalamic presympathetic activity and ultimately neurogenic hypertension. New mouse models were generated where ACE2 and ADAM17 were selectively knocked down from all neurons (AC-N) or Sim1 neurons (SAT), respectively. Neuronal ACE2 deletion revealed a reduction of inhibitory inputs to AC-N presympathetic neurons relevant to blood pressure regulation. Primary neuron cultures confirmed ACE2 expression on GABAergic neurons synapsing onto excitatory neurons within the hypothalamus but not on glutamatergic neurons. ADAM17 expression was shown to colocalize with angiotensin-II type 1 receptors on Sim1 neurons, and the pressor relevance of this neuronal population was demonstrated by photoactivation. Selective knockdown of ADAM17 was associated with a reduction of FosB gene expression, increased vagal tone, and prevented the acute pressor response to centrally administered angiotensin-II. Chronically, SAT mice exhibited a blunted blood pressure elevation and preserved ACE2 activity during development of salt-sensitive hypertension. Bicuculline injection in those models confirmed the supporting role of ACE2 on GABAergic tone to the paraventricular nucleus. Together, our study demonstrates the contrasting impact of ACE2 and ADAM17 on neuronal excitability of presympathetic neurons within the paraventricular nucleus and the consequences of this mutual regulation in the context of neurogenic hypertension. Abstract : Supplemental Digital Content is available in the text.